Dengue NS1 antigen contributes to disease severity by inducing interleukin (IL)‐10 by monocytes. (19th January 2016) - Adikari, T. N.; Gomes, L.; Wickramasinghe, N.; Salimi, M.; Wijesiriwardana, N.; Kamaladasa, A.; Shyamali, N. L. A.; Ogg, G. S.; Malavige, G. N.
Summary: Both dengue NS1 antigen and serum interleukin (IL)‐10 levels have been shown to associate with severe clinical disease in acute dengue infection, and IL‐10 has also been shown to suppress dengue‐specific T cell responses. Therefore, we proceeded to investigate the mechanisms by which dengue NS1 contributes to disease pathogenesis and if it is associated with altered IL‐10 production. Serum IL‐10 and dengue NS1 antigen levels were assessed serially in 36 adult Sri Lankan individuals with acute dengue infection. We found that the serum IL‐10 levels correlated positively with dengue NS1 antigen levels (Spearman's r = 0·47, P < 0·0001), and NS1 also correlated with annexin V expression by T cells in acute dengue (Spearman's r = 0·63, P = 0·001). However, NS1 levels did not associate with the functionality of T cell responses or with expression of co‐stimulatory molecules. Therefore, we further assessed the effect of dengue NS1 on monocytes and T cells by co‐culturing primary monocytes and peripheral blood mononuclear cells (PBMC), with varying concentrations of NS1 for up to 96 h. Monocytes co‐cultured with NS1 produced high levels of IL‐10, with the highest levels seen at 24 h, and then declined gradually. Therefore, our data show that dengue NS1 appears to contribute to pathogenesis of dengue infection by inducing IL‐10 production by monocytes.